Whole genome sequencing and variant discovery in the ASPIRE autism spectrum disorder cohort. Issue 3 (30th May 2019) - Callaghan, Daniel Benjamin; Rogic, Sanja; Tan, Powell Patrick Cheng; Calli, Kristina; Qiao, Ying; Baldwin, Robert; Jacobson, Matthew; Belmadani, Manuel; Holmes, Nathan; Yu, Chang; Li, Yanchen; Li, Yingrui; et al.
Abstract: Autism spectrum disorder (ASD) is a highly heterogeneous genetic disorder with strong evidence of ASD‐association currently available only for a small number of genes. This makes it challenging to identify the underlying genetic cause in many cases of ASD, and there is a continuing need for further discovery efforts. We sequenced whole genomes of 119 deeply phenotyped ASD probands in order to identify likely pathogenic variants. We prioritized variants found in each subject by predicted damage, population frequency, literature evidence, and phenotype concordance. We used Sanger sequencing to determine the inheritance status of high‐priority variants where possible. We report five novel de novo damaging variants as well as several likely damaging variants of unknown inheritance; these include two novel de novo variants in the well‐established ASD gene SCN2A . The availability of rich phenotypic information and its concordance with the literature allowed us to increase our confidence in pathogenicity of discovered variants, especially in probands without parental DNA. Our results contribute to the documentation of potential pathogenic variants and their associated phenotypes in individuals with ASD. Abstract : We sequenced whole genomes of 119 deeply phenotyped autism spectrum disorder (ASD) probands in order to identify likely pathogenic variants. We report five novel de novo damaging variants as well as several likely damaging variants of unknown inheritance. These include two novel de novo variants in the well‐established ASD gene SCN2A : a likely gene damaging splice site variant, and a missense variant predicted to be hypomorphic.